The relationship between study skill and academic achievement in dental students of Tehran University of Medical Sciences - Shirazian Shiva; Arash Mansourian; Mehdi Vatanpour; Fatemeh Tirgar (Tehran University of Medical Sciences, 2015)
Background and Aims: The purpose of the present study was to investigate the relationship between study skills and academic performance of dental students in Tehran University of Medical Sciences. Materials and Methods: 195 dental students at dental faculty of Tehran University of Medical Sciences in 2013 participated in this descriptive-analytical study. Data were collected using Congos´ Study Skills Inventory including six subscales. Grade Point Average (GPA) indicated their academic performance. Data were analyzed using ANOVA and Tukey test. Results: The mean score of students’ study skills were 108 out of 200 with standard deviation of 22.06±0.7. Note taking had a significant correlation with GPA (P=0.015). Conclusion: Since no significant correlation between study skills and academic performance of the students was observed, it seems that there are other dynamics involved in their academic performance which have to be examined.